Rescue of a dislocated intraocular lens with silicone tip aspiration: a novel technique - Haibo Li; Xiuju Chen; Shuxin Cai; Ranqing Lin; Xiaoxin Li (BMC Ophthalmology)
Abstract Background To evaluate the clinical efficacy of a novel surgical technique using a 25-gauge active aspiration of flute needle for treating the dislocation of posterior intraocular lens (IOL). Methods This retrospective study included 12 eyes in 12 patients with posterior dislocated IOL. All patients underwent comprehensive ophthalmic evaluations before surgery. Surgery was performed with three-port pars plana vitrectomy, the dislocated IOL was aspirated to the anterior vitreous by a 25-gauge flute needle, and then managed by different surgical corrections. Comprehensive ophthalmologic assessment was performed preoperatively and postoperatively, including best-corrected visual acuity (BCVA), intraocular pressure (IOP), slit-lamp biomicroscopy and fundus examination. Postoperative assessments were conducted at 1 week, 1 month, and 3 months. Results Twelve eyes were treated. All surgeries were successfully completed using a 25-gauge silicone tip with active aspiration. IOL repositioning without sutures in 1 case (8.3%), IOL repositioning with scleral sutures in 4 cases (33.3%), IOL exchanged with Yamane technique in 4 cases (33.3%) and IOL exchange with scleral sutures in 3 cases (25.0%). The mean follow-up time was 13.08 ± 5.49months (range 5–20 months). The mean BCVA preoperatively was log MAR 0.48 ± 0.33 (range 0.0-1.3), recovered to log MAR 0.34 ± 0.22 (range 0.0-0.7) at three-month postoperatively. The BCVA was improved at the three-month follow-up compared with preoperatively (t = 2.40, P = 0.035 < 0.05). IOP remained stable except for one patient who developed transient high IOP, but well controlled by medications. Conclusions An active aspiration of flute needle with silicon tip provides a simplified, efficient and safe method for IOL dislocation, minimizing the needs of perfluorocarbon liquids as well as intraocular-forceps.